Macroglossia associated with dentofacial deformity treated by orthognathic surgery and simultaneous partial glossectomy: Case report - Everton Luiz de Oliveira Carvalho; Cristiano Elias Figueiredo; Sandro Isaías Santana; Darceny Zanetta-Barbosa; Flaviana Soares Rocha (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2023)
Macroglossia is the abnormally large tongue volume, which, among other causes, may result from increased growth, leading to a size bigger than the oral cavity allows for functional balance. This alteration may be associated with dento-musculoskeletal deformities and instability of orthodontic-surgical treatment, besides favoring the appearance of chewing, speech, and breathing disorders. Surgical tongue reduction is an uncommon procedure indicated for functional or aesthetic correction. This case report involves a patient with relative macroglossia and dentofacial deformity with Angle Class III malocclusion who was also diagnosed with obstructive sleep apnea syndrome. In a single surgical procedure, orthognathic surgery was performed to correct dentofacial deformity using maxillary advancement and expansion, along with advancement genioplasty with basilar horizontal osteotomy and partial glossectomy using the Egyedi-Obwegeser technique. The techniques used were satisfactory for correcting the alterations and restoring function and aesthetics.